Eighth International Workshop on High-Level Parallel Programming Models and Supportive Environments, 2003. Proceedings.
DOI: 10.1109/hips.2003.1196496
|View full text |Cite
|
Sign up to set email alerts
|

A comparison between MPI and OpenMP Branch-and-Bound skeletons

Abstract: This article describes and compares two parallel implementations of Branch-and-Bound skeletons. Using the C ++ programming language, the user has to specify the type of the problem, the type of the solution and the specific characteristics of the Branch-and-Bound technique. This information is combined with the provided resolution skeletons to obtain a distributed and a shared parallel programs. MPI has been used to develop the Message Passing algorithm and for the Shared Memory one OpenMP has been chosen. Com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 9 publications
(9 reference statements)
0
1
0
Order By: Relevance
“…Different research works showed contradictory results about the comparison of the performance of pure multiprocess MPI, pure multithread OpenMP or hybrid MPI-OpenMP implementations of the same algorithm, showing that several factors, such as algorithms, data structures, data size, hardware resources, MPI and OpenMP library implementations, influence their performances [42,43,44,45,46,47,48,49].…”
Section: Speed-up and Efficiency Analysis With Synthetic Datamentioning
confidence: 99%
“…Different research works showed contradictory results about the comparison of the performance of pure multiprocess MPI, pure multithread OpenMP or hybrid MPI-OpenMP implementations of the same algorithm, showing that several factors, such as algorithms, data structures, data size, hardware resources, MPI and OpenMP library implementations, influence their performances [42,43,44,45,46,47,48,49].…”
Section: Speed-up and Efficiency Analysis With Synthetic Datamentioning
confidence: 99%